Contos que o tempo conta: uma experiência de espetáculo com ator em máscara - SILVA, Rogério Vaz da (2023)
The research in question presents the description and analysis of the procedures that were developed due to the creation, assembly and a presentation of the theatical show “Contos que o Tempo Conta”, produced by Company Oficine of Theater, from São Luís, Maranhão, presented in the year of 2019, in the scenic language of Mask’s Theather. I developed a study whery I try to dialou with the most representative foreign and national theorists, on the subject, even incurring in the universe of popular culture. With the intention of better situating the development of the research, I bring, after a reflection on the mask in the theater and groups that use them in their productions, the description, albeit succint, of the history and production of COTEATRO, up to the presente day, culminating in the investigation of the spectable object of study in this work.